2016
DOI: 10.1051/radiopro/2016049
|View full text |Cite
|
Sign up to set email alerts
|

Integration of 3D model THREETOX in JRODOS, implementation studies and modelling of Fukushima scenarios

Abstract: -The radionuclide transport model THREETOX was extended to include the multi-fractional sediments and two-step kinetics. The model was implemented into the decision support system JRODOS where forecasts of marine currents from the operational ocean models were used to predict dispersion of radionuclides. The results of simulation were compared with measurements for the Fukushima-Daiichi case study. The THREETOX model implemented into the JRODOS was applied to the stress test scenario for the ASCÓ nuclear power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The area under study is divided into a number of small grid cells (in this example 1884 × 3712 m 2 ), which allows a larger spatial resolution than in box models. Some examples of Eulerian radionuclide transport models are Breton and Salomon (1995), Harms (1997), Koziy et al (1998), Preller and Cheng (1999), Cetina et al (2000), Bailly du Bois and Dumas (2005), Estournel et al (2012), Periáñez et al (2012), Maderich et al (2016Maderich et al ( , 2017, among many others.…”
Section: Eulerian Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The area under study is divided into a number of small grid cells (in this example 1884 × 3712 m 2 ), which allows a larger spatial resolution than in box models. Some examples of Eulerian radionuclide transport models are Breton and Salomon (1995), Harms (1997), Koziy et al (1998), Preller and Cheng (1999), Cetina et al (2000), Bailly du Bois and Dumas (2005), Estournel et al (2012), Periáñez et al (2012), Maderich et al (2016Maderich et al ( , 2017, among many others.…”
Section: Eulerian Modelsmentioning
confidence: 99%
“…It was shown that the 2-step model reproduces both the adsorption and release kinetics of 137 Cs in the Irish Sea, where it is released from Sellafield nuclear fuel reprocessing plant (Periáñez, 2003b). It was also recently included in THREETOX, which is the marine radionuclide transport model implemented within the JRODOS decision support system (Maderich et al, 2008(Maderich et al, , 2016.…”
Section: Water/sediment Interactions and Other Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…New version of the two dimensional model COASTOX of JRODOS HDM (Zheleznyak et al, 2016) was customized for the reservoirs at Mano Dam-Mano River, at Yokokawa Dam-Ota River, and at Takanokura Dam-Mizunashi River. Three-dimensional model THREETOX of JRODOS HDM (Maderich et al, 2016) was implemented for Yokokawa and Takanokura reservoirs. These reservoirs located in the mountain part of the river watersheds are rather deep (maximum depth up to 30-50 m).…”
Section: Contaminated Water Systems At Fukushima-daiichi Nppmentioning
confidence: 99%
“…As one of the tasks of the EC PREPARE project of the Hydrological Dispersion Module (HDM) of the decision support system -JRODOS (Zheleznyak et al, 2010(Zheleznyak et al, , 2016Gallego et al, 2016;Maderich et al, 2016) was planned to be implemented and tested for the simulation of the radionuclide transport in the water bodies of the region of Japan contaminated by the atmospheric fallout from the Fukushima-Daiichi Nuclear Power Plant (FDNPP).…”
Section: Introductionmentioning
confidence: 99%